The Influence of the Course Review Horay Learning Model Assisted by Video Media on Class IV Science Learning Outcomes - Alamiah, Ayu; Marleni; Riyanti, Henni (Aksara Shofa, 2023)
This study aims to determine the effect of the Course Review Horay learning model supported by video media on science learning outcomes in class IV SD Negeri 43 Palembang. This study used an experimental method with a quasi-experimental design, namely nonequivalent control group design. The population in this research was 42 grade IV students and 42 research samples were taken using the non-probability sampling technique. Data collection used tests with data analysis using the Independent Sample t Test with the help of SPSS version 25. The results showed that there was an influence of the course review learning model. horay to the science learning outcomes of grade IV students at public elementary school 43 palembang. In the Independent Sample t Test, the value of Sig.(2-tailed) 0.020 <0.05 was obtained. Thus it can be concluded that there is a significant effect of the use of the course review horay model on science learning outcomes in class IV SD Negeri 43 Palembang.